Artist and themes: a study on social commentary photographic images / Husaini Yaacob - Yaacob, Husaini (2015)
Social commentary is an alternative method to convey messages to the public with the hope to change their perceptions and attitudes toward certain social issues of ethical, political, moral and even religious. There have been various methods that have been used either in the form of electronic or printed medium. One of the methods has been the photographic images which have been used by the photography artists to convey their messages. This is called as the social commentary. In the advanced countries, social commentary images have long been accepted by the public and has become one of the most powerful medium of communication to alert or trigger the society toward change. In some developing countries as such in Malaysia, the acceptance of social commentary photography among the public is still arguable about the usage of photographic images as a medium of communication which has not been fully accepted and understood by the public. Most of the public has not been aware of what have been posted by the photography artists. Therefore, the photography artworks on social commentary which have been produced by these photography artists in Malaysia have just become an ordinary exhibited materials that do not carry any message or impact to the public. As a consequence, there is a communication gap between the artists and the public in the form of delivering, acceptance and understanding some of the issues which need to be addressed and highlighted through social commentary photography. This study therefore, focuses to investigate the social commentary photography artists and to what extend their messages in the artworks have been understood by the public. This study involves a fully qualitative method by interviewing the Malaysian photography artists to probe details with purposes and intention of why they produce their photographic works to be delivered to the public. The observations in various galleries, exhibitions and analyzing the artists' photography artworks have also been employed. Finally, it is hoped that this study would benefit various levels of people such as artists, different societies, personnel in government and public sectors to provide great impact and awareness to them as photographic images have become one of the most powerful medium in conveying and delivering various messages to public in this digital era.